Children’s Perception and Learning Skills: Implications in Kindergarten Architecture (Journal of Engineering, 2026)
Kindergarten architecture plays an important role in shaping children’s perception and learning. However, many designs still fail to systematically translate educational theories into tangible spatial solutions. This gap highlights the research problem addressed in the present study as the absence of integrated architectural indicators that connect children’s perceptual development, learning styles and philosophical ideas with the design of kindergartens. The aim of the paper is to develop a consistent set of design indicators which could lead to the creation of a captivating learning environment by the architects as well as the educators. In the methodological approach, the study determines six types of learning styles: cognitive, social, sensorimotor, cooperative and play-based learning. It resorts to a literature-based synthesis of theories of perception and learning with focus on the preoperational stage, simultaneously incorporating the philosophical and pedagogical work of the theorists who first began to explore the concepts, namely, Froebel, Montessori, Decroly, McMillan and Dewey. All these theoretical considerations resulted in the development of a set of abstract architectural indicators that have the priority to provide the basis of their practical application to the kindergarten environment. Such indicators were applied to Šmartno Kindergarten to demonstrate how abstract concepts can be translated into architectural practices. The research concluded that subjecting the kindergarten design to the theories of perception and learning promotes the curiosity, creativity and the overall development of children, in addition to supplying the architects or the designers with pragmatic guidelines for early-childhood design.